Contraceptive knowledge and attitude of Sabah married women - Ahmad, Nor Zehan; Racheal Pirry, Precylla; Li-Yoong, Tang; Suchi, Umiaziente; Badri, Intan Baiduri; Zaini, Noor Hanita (Asia Pacific Higher Learning Sdn Bhd., Lincoln University College, 2025)
Background: An unplanned pregnancy was identified as a major public health concern worldwide in developed and developing countries. Since nurses are frontline healthcare providers of reproductive health counselling in Malaysia, the present study evaluated the level of knowledge and attitude toward contraception among married women in Sabah, Malaysia. Methods: A cross-sectional study was conducted among 254 women who resided in the Interior and West Coast Division of Sabah, Malaysia. Knowledge and attitude on the contraceptive questionnaire were administered to participants via convenience sampling. The instruments had high level of reliability, with a Cronbach's alpha coefficient of 0.73 for both knowledge and attitude. Results: The participants' mean age was 35.20 7.189 years. Most respondents (n=92, 36.2%) had poor knowledge of contraceptives, while (n=162, 63.8%) showed a satisfactory attitude towards contraception. Age group, residential address, monthly income, and number of children were significantly associated with women's knowledge level (p>0.05). Meanwhile, the monthly income and number of children were significantly associated with attitude level of women residing in Sabah (p<0.05). Conclusion: A worryingly high percentage of women in Sabah demonstrated poor knowledge, despite showing a satisfactory attitude. This crucial information can guide targeted interventions to improve contraceptive awareness and uptake. Community health nurse and nurse-midwives can leverage these findings to design targeted, culturally sensitive education and counselling interventions, particularly for lower-income, multiparous, and rural women, to improve contraceptive literacy and uptake.